2014
DOI: 10.1111/mmi.12847
|View full text |Cite
|
Sign up to set email alerts
|

Structure and function of enterotoxigenic Escherichia coli fimbriae from differing assembly pathways

Abstract: Pathogenic enterotoxigenic Escherichia coli (ETEC) are the major bacterial cause of diarrhea in young children in developing countries and in travelers, causing significant mortality in children. Adhesive fimbriae are a prime virulence factor for ETEC, initiating colonization of the small intestinal epithelium. Similar to other Gram-negative bacteria, ETEC express one or more diverse fimbriae, some assembled by the chaperone-usher pathway and others by the alternate chaperone pathway. Here we elucidate structu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
30
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 26 publications
(34 citation statements)
references
References 52 publications
(77 reference statements)
3
30
0
Order By: Relevance
“…ETEC fimbriae such as CS2, CFA/I, and CS20 require <15 pN unwinding force, despite differences in their assembly mechanism (see Table S1 and our previous work (24,26)); UPEC and meningitis-associated strains of E. coli express fimbriae requiring 21-30 pN of unwinding force (33,39,42); however, Type 3 fimbriae expressed by K. pneumonia in the respiratory tract require 66 pN of unwinding force (43). One should also note that the T4 fimbriae expressed by Streptococcus pneumonia, which also colonize the respiratory tract, are significantly stiffer than UPEC-and ETEC-expressed fimbriae (45).…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…ETEC fimbriae such as CS2, CFA/I, and CS20 require <15 pN unwinding force, despite differences in their assembly mechanism (see Table S1 and our previous work (24,26)); UPEC and meningitis-associated strains of E. coli express fimbriae requiring 21-30 pN of unwinding force (33,39,42); however, Type 3 fimbriae expressed by K. pneumonia in the respiratory tract require 66 pN of unwinding force (43). One should also note that the T4 fimbriae expressed by Streptococcus pneumonia, which also colonize the respiratory tract, are significantly stiffer than UPEC-and ETEC-expressed fimbriae (45).…”
Section: Discussionmentioning
confidence: 96%
“…Interestingly, fimbriae expressed in a specific microenvironment exhibit similar properties; for example, the unwinding force of CS20 is more similar to that of CFA/I than to that of P fimbriae, even though CS20 antigens share higher amino acid identity with the pilins of P fimbriae (26). Thus, the structural and biomechanical characteristics of fimbriae appear to play a determinant role in E. coli colonization and pathogenesis in a specific organ, i.e., E. coli strains sharing a common niche express fimbriae with similar biophysical properties (26).…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…The model is also consistent with an axial hole (~ 2 nm), which is only visible on the electron micrograph of thicker fimbriae. Thick helical fimbriae can be stretched under certain in vitro conditions (117) or by using force to unwind the helix (118), accompanied by conformational changes in fimbrial subunits. It has been suggested that fimbrial stretching occurs in vivo to adjust and coordinate the lengths of the few hundred fimbrial threads anchoring the colonizing bacteria that are submitted to the intestinal peristalsis and its resulting shear force (119).…”
Section: Fimbrial Structuresmentioning
confidence: 99%
“…Recent studies suggest that the quaternary structure of a fimbrial shaft plays an additional deterministic role in colonization, inasmuch as the shaft of certain ETEC fimbriae, as well as those of other pathogenic E. coli, is adapted to organ-specific biomechanical and structural features. Despite their differences in biogenesis and assembly processes, when analyzed biomechanically, ETEC-expressed fimbriae unwind at a characteristic low-unwinding steady force of Ͻ20 pN (7,8), while fimbriae expressed by extraintestinal pathogenic E. coli (ExPEC), such as type 1, P, and S fimbriae, require a steady force of Ͼ20 pN to unwind (7,(9)(10)(11)(12).…”
mentioning
confidence: 99%